The Use of Mobile Technology in the Marketing of Therapeutic Tourist Sites: A Critical Analysis - Muhamad Fazil, Ahmad; Mohammed, Habes; Mahmoud, Alghizzawi; Said, A. Salloum (2018)
The main aim of this study is to provide practitioners and researchers with some insights into the users’ level of smartphone marketing of therapeutic tourism with more focus on the Arab world. Marketing of therapeutic tourism has not been addressed substantially as a research area and very little research exist about the use of technologies in tourism marketing in general and the Arab world in specific. Generally, this work will contribute to the Arab behavior in the adoption of smartphone marketing in tourism research. Specifically, this study will add to the body of knowledge for the future development of smartphone marketing in the therapeutic tourism in Jordan.